ANALISIS SWOT SEBAGAI DASAR PENGUATAN IMPLEMENTASI MBS: STUDI KASUS DI SD NEGERI 6 PANJER - Chindytia; Ni Kadek Helen Martha Dewi; I Made Ari Suantara; I Gusti Agung Halena Mas Wiratami (STKIP Subang, 2026)
This study aims to analyze the internal and external conditions of schools in supporting the implementation of School-Based Management (SBM) using SWOT analysis at SD Negeri 6 Panjer. This research applies a qualitative case study approach through observation and interviews. The results indicate that the school’s strengths include literacy, numeracy, character education programs, and community support, while weaknesses involve limited teacher technological competence and student behavioral issues. Opportunities come from parental support and technological developments, while threats arise from social environments and diverse family backgrounds. The SWOT analysis produces strategies such as improving teacher competence, strengthening character education, optimizing programs, and enhancing collaboration with parents to ensure more effective and sustainable SBM implementation.